(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Every individual is unique and has infinite potentials. However such potential remains untapped it we do not garner them rightfully. Talents can be aptly used when the right environment is created and necessary capacity building measures are adopted to nurture them. Among the numerous measures that can be adopted, conducting trainings to enhance knowledge level, skills and competency of employees are significant. A new book entitled ‘TRAINING AND DEVELOPMENT’ by Nishant Uppal has arrived on the shelf. It is published by Pearson Education, India. A succinct discourse on the book entails merit from the perspective of many stakeholders. The book contains a total of seven chapters. The first chapter gives an overall idea to the reader on the general topic of the book and is named as ‘Introduction to the Concept of Employees Training and Development’.